Social determinants of financial stress and association with psychological distress among young adults 18–26 years in the United States - Anaiya Nasir; Umair Javed; Kobina Hagan; Ryan Chang; Harun Kundi; Zahir Amin; Sara Butt; Sadeer Al-Kindi; Sadeer Al-Kindi; Zulqarnain Javed; Zulqarnain Javed (Frontiers in Public Health)
IntroductionFinancial stress (FS) during young adulthood may have lasting effects on financial security, physical health, and overall wellbeing. This study examines the burden, social determinants and mental health consequences of experienced FS among young adults in the United States, based on objective measures of financial stress.MethodsWe studied young adults aged 18–26 years using pooled data from the 2013–18 National Health Interview Survey. FS was assessed as an aggregate score (6–24) based on worry about six life tasks: paying for: monthly bills, housing expenses, healthcare, illness/accident, maintaining standard of living, saving money for retirement. Individuals in the highest quartile of the score were defined as having high FS. Psychological distress (PD) was measured using the six-item Kessler Psychological Distress Scale (K6); high PD was defined as total K6 score ≥13. Multivariable ordinal and logistic regression models were used to assess key social determinants of FS and the association between FS and PD, respectively.ResultsStudy sample included 19,821 individuals aged 18–26 years (34 million annualized). Overall, 17% (5.8 million nationally) of young adults reported high FS. Female, non-Hispanic Black and Hispanic, low income/low education, uninsured, non-citizen and comorbidities were associated with high FS burden. In fully adjusted models, high FS was associated with over 6-fold (OR = 6.17, 95% CI 4.43–8.61) higher risk of high PD.DiscussionOne in six young adults in the US experiences high FS, which portends high risk of PD. These findings should inform stakeholder deliberations to identify and mitigate the unintended mental health consequences of FS in this vulnerable population.